Punctuation Practice in the Antidotary in G.U.L. MS Hunter 513 (ff.37v-96v) - Marqués Aguado, Teresa (Miscelánea: A Journal of English and American Studies, 2009)
The study of punctuation practices in Old and Middle English texts has been traditionally neglected by many scholars on the grounds of their apparent ambiguity and lack of consistency. As a consequence, punctuation has been silently modernised in editions of Old and Middle English texts. Yet, recent studies have shown that there is certain regularity in the insertion of punctuation marks, and different methods have been put forward to modernise punctuation when required. The aim of this article is to analyse the punctuation system of the Antidotary contained in Glasgow University Library, MS Hunter 513 (ff.37v - 96v). To thisend, the uses of each punctuation mark will be discussed and classified in terms of the function they display. In view of these uses, functional equivalents will be proposed for the modernisation of its punctuation.
Keywords: punctuation; Middle English; medicine; modernisation; Antidotary